TAHAPAN PRODUKSI OLAHAN IKAN KEUMAMAH SIAP SAJI SEBAGAI PENGEMBANGAN PRODUK DI UD. SAMUDERA MIRJA - Sariana sariana; Muhammad agam thahir; Dini Marliana; T Hamdan; Sarita ayu; Syahrul muhharram; Dimas kusmayadi; Fadhli fadhli (Marine Kreatif, 2022)
Keumamah fish or wooden fish is one of Aceh's traditional preparations made from the main raw material of tuna, skipjack tuna which is dried in the sun. The purpose of this activity is to find out the stages of processing ready-to-eat keumamah fish so that the resulting product is more hygienic and can increase consumer attractiveness. Wood fish (keumamah) is generally processed from tuna (Euthynnus affinis) in a very simple way. UD. Samudera Mirja manages wood fish (keumamah), salted fish, fish meal, and shabu prawns. Researchers are directly involved in every activity in the field and carry out direct observations systematically. This processing unit operates with production levels that change every day depending on the availability of raw materials in each production. Processing of ready-to-eat wooden fish (keumamah) at UD. Samudera Mirja is very simple with packaging that still uses ordinary plastic cups. Keumamah packaging that uses plain plastic cups is replaced with plastic bottle packaging that has a label on each package and is coated with aluminum foil and in terms of taste it has many flavor variants, namely; original taste, spicy taste and sweet taste. By making new innovations in the processing of ready-to-eat keumamah fish that can create new flavors with more attractive packaging forms so that it can get a lot of consumer interest.